Evolution of epidemiological characteristics of infective endocarditis in Greece. (May 2021) - Giannitsioti, Efthymia; Pefanis, Angelos; Gogos, Charalampos; Lekkou, Alexandra; Dalekos, Georgios N.; Gatselis, Nikolaos; Georgiadou, Sara; Nikou, Paraskevas; Vrettou, Agathi; Rigopoulos, Angelos; Tryfonopoulos, Christos; Tsaganos, Thomas; et al.
Highlights: IVDA and HIV patients with IE emerged during the era of economic crisis. S. aureus and MRSA predominated in the youth and Enterococci in the elderly. Compared to previous cohort, rheumatic fever decreases and renal disease increases. Both cardiac surgery and compliance with antimicrobial treatment promoted survival. Abstract: Objective: The clinical profile, management and outcome of infective endocarditis (IE) may be influenced by socioeconomic issues. Methods: A nationwide prospective study evaluated IE during the era of deep economic crisis in Greece. Epidemiological data and factors associated with 60-day mortality were analyzed through descriptive statistics, logistic and Cox-regression models. Results: Among 224 patients (male 72.3%, mean age 62.4 years), Staphylococcus aureus (n = 62; methicillin-resistant S. aureus (MRSA) 33.8%) predominated in the young without impact on mortality ( p = 0.593), whilst Enterococci (n = 36) predominated in the elderly. Complications of IE were associated with mortality: heart failure [OR 2.415 (95% CI: 1.159–5.029), p = 0.019], stroke [OR 3.206 (95% CI: 1.190–8.632), p = 0.018] and acute kidney injury [OR 2.283 (95% CI: 1.085–4.805), p = 0.029]. A 60-day survival benefit was solely related to cardiac surgery for IE during hospitalization [HR 0.386 (95% CI: 0.165–0.903), p = 0.028] and compliance with antimicrobial treatment guidelines [HR 0.487 (95% CI: 0.259–0.916), p = 0.026]. Compared with a previous country cohort study, history of rheumatic fever and native valve predisposition had declined, whilst underlying renal disease and right-sided IE had increased ( p < 0.0001); HIV infection had emerged ( p = 0.002). No difference in rates of surgery and outcome was assessed. Conclusions: A country-wide survey of IE highlighted emergence of HIV, right-sided IE and predominance of MRSA in the youth during a severe socioeconomic crisis. Compliance with treatment guidelines promoted survival.